Improving Motoric Skills Through Activities to Stick Patterned Buttons Aged 5-6 years at Ra-arrosyad prambon: Peningkatkan Kemampuan Motorik Halus Melalui Kegiatan Menempel Kancing Berpola Usia 5-6 Tahun Di Ra-Arrosyad Prambon - Livia Nuranisyah; Choirun Nisak Aulina (Wadah Inovasi Indonesia, 2022)
This study discusses the application of patterned buttons to improve fine motor skills of children aged 5-6 years at RA Arrosyad Prambon. The purpose of this study was to determine the level of fine motor skills of children aged 5-6 years at RA Arrosyad Prambon. This research was conducted using classroom action research methods. The research design used is the design by John Elliot's Model, which includes four plots of action planning, action implementation, observation or observation, and action reflection. The research subjects were 12 children. The research data consisted of primary and secondary. Data collection techniques using observation, interviews, and documentation. This study shows an increase in children's fine motor skills. This is evidenced by the implementation through three cycles. The results in the pre-cycle 35.42% then in the first cycle to 56.25% in the second cycle 88.5%. The results obtained in each cycle increased through the activity of attaching patterned buttons. The implication of this research is that the learning process involves sticking patterned buttons as an alternative for improving the quality of learning